EFEKTIVITAS IMPLEMENTASI PJBL DALAM MENDORONG KREATIVITAS SISWA PADA PEMBELAJARAN SENI TARI DI SMAN 1 GEDEG KABUPATEN MOJOKERTO - Favilia, Delvi; Warih Handayaningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model in improving students’ creativity in dance subjects at SMAN 1 Gedeg, Mojokerto Regency. Creativity is an essential aspect of dance education; however, it is often insufficiently facilitated due to conventional learning approaches. The research method used was descriptive qualitative research focusing on an in-depth description of phenomena through data collection from informants using interviews, observations, and documentation. The results of the study indicate that the implementation of PjBL through group-based creative dance projects significantly improved students’ creativity. The creativity indicators include fluency, flexibility, originality, and elaboration in developing dance movements. This project-based learning process encourages students to actively explore, collaborate, and solve problems in composing dance works. The conclusion of this study is that the implementation of PjBL is effective as an interactive and innovative alternative learning model to foster students’ dance creativity at SMAN 1 Gedeg.